ANALYZING THE EFFECTS OF PREGNANCY AND CHILDBIRTH ON WOMEN’S MENTAL HEALTH IN CHILAS, GILGIT-BALTISTAN: A CROSS-SECTIONAL STUDY - Sara Jamil Khan; Dr Uzma Almas; Dr Maria Khan; Romana Chambeli; Sundam; Umme Habiba (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Factors such as inadequate healthcare access and a lack of social support amplify the prevalence of mental health concerns including anxiety and depression among women worldwide during and after pregnancy. There is an increased risk of mental health disorders during and after pregnancy for women in rural areas like Chilas District Diamer Gilgit-Baltistan, where cultural norms are strong and health services are few. Objective Among women in Chilas, District Diamer, Gilgit-Baltistan, we aimed to determine the frequency of postpartum depression and anxiety and the variables that were linked with it. Methods Using the Edinburgh Postnatal Depression Scale (EPDS) and the Generalised Anxiety Disorder 7-item (GAD-7) to screen for depression and anxious symptoms, a cross-sectional study was carried out among 200 women of reproductive age. We used logistic regression models to look for connections between people’s demographics, the method of delivery, and their social support system and mental health outcomes. Results Anxiety disorders were present in 29% of people, whereas depression affected 37%. Postpartum depression was more prevalent (65% of depressed women). An individual’s likelihood of experiencing mental health concerns was significantly increased when they lacked education (OR = 2.3, CI: 1.4-3.8), had a poor income (OR = 2.7, CI: 1.8-4.2), gave birth at home (OR = 1.9, CI: 1.2-3.1), and had lower social support (OR = 2.1, CI: 1.4-3.2). Conclusion Socioeconomic status, level of education, and access to healthcare all have a role in the high rates of depression and anxiety experienced by women in Chilas. In order to tackle these issues, we must implement interventions that enhance healthcare accessibility, education, and social support. Community mental health therapies that are sensitive to Chilas’s unique cultural and economic circumstances should be the subject of future studies.